Sally Grainger: The Story of Garum: Fermented Fish Sauce and Salted Fish in the Ancient World - Dalby, Andrew (Petits Propos Culinaires, 2021)
Sally Grainger: The Story of Garum: Fermented Fish Sauce and Salted Fish in the Ancient World: Routledge, 2021: 301 pp., hardback, £120.00.